2020
DOI: 10.1111/jcmm.16134
|View full text |Cite
|
Sign up to set email alerts
|

Gracillin shows potent efficacy against colorectal cancer through inhibiting the STAT3 pathway

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
(79 reference statements)
0
11
0
Order By: Relevance
“…At the same time, we found that the paclitaxel-treated mice died or became emaciated in the late treatment period, whereas the gracillin-treated mice did not. From the H&E staining results of liver, lung, heart, and kidney of mice, it can be found that gracillin is basically non-toxic to mice, and literature reports can also prove this result ( 24 ). Study on the anti-tumor mechanism, absorption, and metabolism of gracillin in vivo will become the direction of our future research.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…At the same time, we found that the paclitaxel-treated mice died or became emaciated in the late treatment period, whereas the gracillin-treated mice did not. From the H&E staining results of liver, lung, heart, and kidney of mice, it can be found that gracillin is basically non-toxic to mice, and literature reports can also prove this result ( 24 ). Study on the anti-tumor mechanism, absorption, and metabolism of gracillin in vivo will become the direction of our future research.…”
Section: Discussionmentioning
confidence: 87%
“…Chen found that gracillin induces human leukemia HL60 cell apoptosis and cell cycle G1 block via oxidative stress pathway ( 21 ); Min found that gracillin disrupts complex II-mediated mitochondrial function by inactivating succinate dehydrogenase, which resulted in decreased mitochondrial membrane potential, oxidative phosphorylation, and ATP production, at the same time, increased mitochondrial ROS production ( 22 ). And then they found that gracillin exerts a powerful anti-tumor effect mainly by inhibiting the production of bioenergy mediated by glycolysis and oxidative phosphorylation in tumor cells ( 23 ).Yang found that Gracillin exhibits a powerful anti-colorectal cancer effect by inhibiting the STAT3 pathway ( 24 ). The anti-tumor potential of gracillin is obvious, but there are relatively few studies on anti-tumor mechanisms, mainly involving apoptosis and energy metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Drug targets of the active ingredients in Chonglou (dioscin ( Tao et al, 2018 ; Ding et al, 2020 ; Wu et al, 2020 ), gracillin ( Liu et al, 2021 ; Yang J. et al, 2021 ; Yang L. et al, 2021 ), polyphyllin I ( Chang et al, 2017 ; Tian et al, 2020 ; Lai et al, 2021 ; Shen et al, 2021 ), polyphyllin II ( Niu et al, 2020 ), polyphyllin III ( Zhou et al, 2021 ), polyphyllin VI ( Liu et al, 2020 ; Teng et al, 2020 ), polyphyllin VII ( He et al, 2020 ; Zhao et al, 2021 ) and polyphyllin H) were collected by using the online tools ( Su et al, 2019 ), including PubChem ( https://pubchem.ncbi.nlm.nih.gov/ ), Swiss Target Prediction ( http://www.swisstargetprediction.ch/index.php ) and TargetNet ( http://targetnet.scbdd.com/home/index/ ).…”
Section: Methodsmentioning
confidence: 99%
“…[62] The other sources of gracillin include Aconitum carmichaeli, [63] Costus speciosus, [64] Paris polyphylla Smith var. yunnanensis, [65] Reineckia carnea, [66] and Rhizoma paridis. [67] Various studies state that all these plants have anticancer properties along with other therapeutic benefits [65,[68][69][70][71] (Table 1).…”
Section: Botanical Sources Of Gracillinmentioning
confidence: 99%